The Reality of Humanitarian Social Values: Tolerance, Empathy, and Peace in Elementary School - Fadillah, Anggun Nur; Ferawati, Efa; Novita, Tiara Nissa; Hayati, Auliya Aenul; Permana, Faisal Rahmat; Malonisio, Manuel (Universitas Muhammadiyah Surakarta, 2026)
This study explores the internalization of humanitarian social values—tolerance, empathy, and peace among elementary school students in Indonesia. While national curricula emphasize character education, there remains a disconnect between policy and classroom practice. Using a mixed-methods approach, this research combined quantitative surveys with qualitative classroom observations and teacher interviews. The instrument’s validity and reliability were confirmed through Pearson’s correlation and Cronbach’s Alpha (α = 0.826), and descriptive statistics revealed high scores in tolerance (M = 32.73), moderate in empathy (M = 29.47), and low in peacefulness (M = 25.63). However, qualitative findings uncovered behavioral gaps. Students frequently showed blame-oriented responses, emotional disengagement, and minimal conflict resolution skills. Thematic analysis, supported by inter-coder agreement and member checking, revealed that moral knowledge was rarely translated into daily behavior. This misalignment indicates that character education is often limited to declarative instruction without experiential or emotional reinforcement. The study concludes that schools must adopt participatory and emotionally grounded pedagogies to bridge this value-practice gap. Recommendations include integrating social-emotional learning (SEL), teacher training in inclusive strategies, and aligning school culture with national moral objectives. The findings underscore the importance of transforming moral education from abstract knowledge into lived, embodied practices that shape students' everyday social interactions.